Mediating role of triglyceride glucose-related index in the associations of composite dietary antioxidant index with cardiovascular disease and mortality in older adults with hypertension: a national cohort study - Zhang, Yajie; Liu, Yingying; Qiao, Huiquan; Ma, Qiongqiong; Zhao, Bing; Wu, Qian; Li, Hongyu (Frontiers in Nutrition, 2025)
BackgroundThis research investigates the relationships between the composite dietary antioxidant index (CDAI) and the likelihood of cardiovascular disease (CVD) and mortality in older adults with hypertension. Utilized data from the National Health and Nutrition Examination Survey (NHANES) to investigate the potential mediating role of the triglyceride-glucose (TyG) index in these relationships.MethodsA cohort of 5,276 participants, aged 65 years or older and diagnosed with hypertension, was extracted from the NHANES database. The main outcomes examined were the odds of CVD and mortality, utilizing data from the National Center for Health Statistics (NCHS). Multivariate logistic regression models were utilized to evaluate the relationship between CDAI and CVD. Cox proportional hazards regression models and Kaplan–Meier survival curves were utilized to analyze the relationship between CDAI and mortality. Mediation analysis was conducted to assess the potential intermediary role of TyG-related indicators—specifically TyG, TyG-BMI, TyG-WC, and TyG-WHtR— in the connection between CDAI and mortality.ResultsThe mean CDAI for the study participants was 1.88 ± 3.90, and the average age was 74.15 ± 5.96 years. During an average follow-up duration of 109.51 months, 4,712 cases of CVD and 725 recorded deaths were observed. In the fully adjusted models, CDAI showed a negative association with both CVD (Odds Ratio [OR] = 0.94, 95% Confidence Interval [CI] = 0.92–0.97) and mortality (Hazard Ratio [HR] = 0.95, 95% CI = 0.93–0.97). Mediation analysis indicated that the TyG-BMI, TyG-WC, and TyG-WHtR indices accounted for 33.1%, 34.3%, and 19.1% of the relationship between CDAI and mortality, respectively.ConclusionA higher CDAI demonstrated an inverse association with both CVD and mortality in elderly hypertensive individuals. The relationship was partially mediated by TyG-related indices, indicating that increased antioxidant intake may lead to improved health outcomes and a decreased risk of poor prognosis in this population.